Reduction in J.-L. Marion’s phenomenology - Roggero, Jorge Luis (ARFIL y UNL, 2020)
Which is the statute of reduction in Marion's work? This article aims to clarify this fundamental operation in the phenomenology of donation by establishing its relationship with the epoché understood in the Heideggerian way of a fundamental attunement.